Polymyxin is isolated from marine Bacillus polymyxa bacteria and its effect in pathogenic bacteria - قره علي, أحمد; العلي, بدر; حمود, رامي (Latakia University Journal -Biological Sciences Series, 2020)
The organic extract of supernatant of marine bacteria isolate (Bacillus polymyxa) was obtained . This bacteria was isolated from the coastal water from Afami site - Lattakia. The polymyxin antibiotic extract was isolated in a pale greasy and powder form after crystallization and purification processes. The inhibitory activity of polymyxin antibiotic was tested against four bathogenic bacteria, Gram-positive bacteria (Streptococcus pneumoniae and Staphylococcus aureus) and Gram- negativ bacteria (Escherichia coli and Klebsiella pneumonia), which were isolated from hospital laboratory of Tishreen University in Lattakia, by the well diffusion method. The results showed higher inhibitory effect towards Gram-negative bacteria than Gram-positive bacteria. Depending on these results, we can say that the extracts of marine Bacillus polymyxa were expected to be potential resources of natural antibiotic products against pathogenic bacteria in the future.